DEMOGRAPHIC COMPOSITION OF THE POPULATION - Dilshoda Inomjonova (Journals Park Publishing, 2022)
This article covers demography, the scientific practical basis of demography, the essence of the concept of demography, the basis of demography and the laws of study, its development, demographic processes, reproduction of the population, important aspects of demographic processes.
Keywords: sexual structure; age structure; age-dependency